South Pole Station ozonesondes: variability and trends in the springtime Antarctic ozone hole 1986–2021 - B. J. Johnson; P. Cullis; J. Booth; I. Petropavlovskikh; G. McConville; B. Hassler; G. A. Morris; C. Sterling; S. Oltmans (Atmospheric Chemistry and Physics, 2023)
Balloon-borne ozonesondes launched weekly from South Pole Station (1986–2021) measure high-vertical-resolution profiles of ozone and temperature from the surface to 30–35 km altitude. The launch frequency is increased in late winter before the onset of rapid stratospheric ozone loss in September. Ozone hole metrics show that the yearly total column ozone and 14–21 km partial column ozone minimum values and September loss rate trends have been improving (less severe) since 2001. The 36-year record also shows interannual variability, especially in recent years (2019–2021). Here we show additional details of these 3 years by comparing annual minimum profiles observed on the date when the lowest integrated total column ozone occurs. We also compare the July–December time series of the 14–21 km partial column ozone values to the 36-year median with percentile intervals. The 2019 anomalous vortex breakdown showed stratospheric temperatures began warming in early September followed by reduced ozone loss. The minimum total column ozone of 180 Dobson units (DU) was observed on 24 September. This was followed by two stable and cold polar vortex years during 2020 and 2021 with total column ozone minimums at 104 DU (1 October) and 102 DU (7 October), respectively. These years also showed broad near-zero-ozone (loss saturation) regions within the 14–21 km layer by the end of September which persisted into October. Validation of the ozonesonde observations is conducted through the ongoing comparison of total column ozone measurements with the South Pole ground-based Dobson spectrophotometer. The ozonesondes show a more positive bias of 2 ± 3 % (higher) than the Dobson following a thorough evaluation and homogenization of the long-term ozonesonde record completed in 2018.